Evaluation on the effectiveness of 2-deoxyglucose-6-phosphate phosphatase (DOGR1) gene as a selectable marker for oil palm (Elaeis guineensis Jacq.) embryogenic calli transformation mediated by Agrobacterium tumefaciens - Dayang Izawati, Abang Masli; Abdul Masani, Mat Yunus; Ismail, Ismanizan; Ghulam Kadir, Ahmad Parveez (Frontiers in Plant Science, 2015)
DOGR1, which encodes for 2-deoxyglucose-6-phosphate phosphatase, has been used as a selectable marker gene to produce transgenic plants. In this study, a transformation vector, pBIDOG, which contains the DOGR1 gene, was transformed into oil palm embryogenic calli mediated by Agrobacterium tumefaciens strain LBA4404. Transformed embryogenic calli were exposed to 400 mg l–1 2-deoxyglucose (2-DOG) as the selection agent. 2-DOG resistant tissues were regenerated into whole plantlets on various regeneration media containing the same concentration of 2-DOG. The plantlets were later transferred into soil and grown in a biosafety screenhouse. PCR and subsequently Southern blot analyses were carried out to confirm the integration of the transgene in the plantlets. A transformation efficiency of about 1.0% was obtained using DOGR1 gene into the genome of oil palm. This result demonstrates the potential of using combination of DOGR1 gene and 2-DOG for regenerating transgenic oil palm.